The Effect of National Culture on the Choice of Entry Mode - Kogut, Bruce; Singh, Harbir (Journal of International Business Studies, 1988)
Characteristics of national cultures have frequently been claimed to influence the selection of entry modes. This article investigates this claim by developing a theoretical argument for why culture should influence the choice of entry. Two hypotheses are derived which relate culture to entry mode choice, one focusing on the cultural distance between countries, the other on attitudes towards uncertainty avoidance. Using a multinomial logit model and controlling for other effects, the hypotheses are tested by analysing data on 228 entries into the United States market by acquisition, wholly owned greenfield, and joint venture. Empirical support for the effect of national culture on entry choice is found.